Mass transport to and within porous electrodes. Linear sweep voltammetry and the effects of pore size: The prediction of double peaks for a single electrode process - Henstridge, M; Dickinson, E; Compton, R (2012)
We simulate an electrode modified with a conducting porous film, where the electrolysis occurs both at the surface of the film and within it, in order to study the effect of pore size on the peak current in linear sweep voltammetry. For redox systems with reversible electrode kinetics we find that for both very large and very small pores the peak current is given by the Randles-Šev ik equation. For intermediate pore size, however, we observe a greatly enhanced peak current. When considering systems with irreversible electrode kinetics a very similar pattern is observed, except for the case of very small pores. In this case the peak current is actually smaller than expected from the Randles-Šev ik equation because the peak splits into two distinct peaks; one due to "thin layer" diffusion within the film and another caused by planar diffusion from bulk solution. The experimental implications of this observation are significant given the widespread use of modified electrodes for analysis. © Pleiades Publishing, Ltd., 2012.